Peran Pekerja Sosial dalam Memberikan Pelayanan Sosial pada Lanjut Usia - Aris Hilmawan; Almisar Hamid (SOSIAL : Jurnal Ilmiah Pendidikan IPS, 2024)
The aging population will be a problem if the elderly have problems. The increasing number of problems elderly people confront may turn them into persons who need help to maintain their standard of living. Government-run institutions include the Tresna Werdha Social Service Center (BPSTW), where social workers play a crucial role in the delivery of social services. Social facilities for the elderly frequently face challenges with their residents' mobility, emotional and physical health, need for caregivers for daily activities, trouble adjusting, and lack of social interaction. Because it explains the role that social workers play in assisting the elderly, researchers are interested in studying "The Role of Social Workers in Providing Social Services to the Elderly in PSTW". The strategy used gives an objective account of the reality in the field. The descriptive "Qualitative" approach is a research methodology intended to offer a comprehensive examination of the function social workers perform in providing social support to the elderly. To understand and explain the phenomenon is its aim. This study's author focuses on the role that social workers play and the difficulties that they face in providing social services to WBS. Among the research findings gleaned from the interviews are social